KAJIAN AWAL TERHADAP KONDISI PENCAHAYAAN ALAMI PADA BANGUNAN RUMAH LIMAS ! . (Preliminary Study on Natural Lighting Condition of Limas Shaped House Building) - W. Putri, Alrikagustl; Wahyuni, Yuni Sri (Tesa Arsitektur, 2012)
Indonesias tropical climate has a significant potential in providing natural lighting to design buildings. Umas or pyramidal shaped house In its original condition (has not been modified/engineered), meaning that it is made of wood, having original elements and building design with openings Is believed to possess natural lighting for a construction that is assumed inadequate for productive activities. Seeing the existing activity pattern, a Ilmas house is not aimed just to rest but it is also to perfonn other activities, such as reading and working in the room. These activities require adequate support of room lighting. This study was conducted to verify the assumption telling that the lighting system of a limas house is insufficient productive activities during the day time. The study used a computerized simulation and field measurements to see the a priori condition of the limas house as the object of the study and then to compare the results of measurements. The result showed that the level of natural lighting In the house was almost the same that was 150 lux In average. This reinforced the assumption that the natural lighting level of the studied Ilmas house was insufficient to support productive activities In the day time. To get solutions in improving natural lighting condition of limas house, further studies are needed.